Co-infections of hepatitis B patients with other hepatitis viruses and their serological, biological and prognostic markers - Hudu Abdullahi, Shuaibu (2017)
Hepatitis B patients, who are co-infected with other hepatitis viruses, are associated with more severe infection and higher mortality than in mono-infection therefore, fulminant hepatitis with co-infection is more likely than with infection with HBV alone. Hepatitis B is a non-cytopathic virus therefore; immune response that takes place in the liver against the virus is responsible for the inflammation of the hepatocytes, hence referred to as “hepatitis”. This inflammatory process triggered by the virus is mediated by human cytokines, thereby determining the severity or otherwise of the infection the failure of suppressing hepatitis B virus replication is thought to be as a result of ineffective cytokine response. Therefore, this study aimed to determine the clinical, serological and biochemical and genetic diversity of hepatitis B and co-infection with other hepatitis viruses and propose novel prognostic markersof cirrhosis and acute deterioration of chronic hepatitis B infection. A total of 82 patients’ blood samples and clinical data were collected from May, 2015 to May, 2016 at the Hepatology Department of Hospital Selayang from chronic hepatitis B patients. All the samples were tested for hepatitis B sero-markers and hepatitis C, D, and E antigens using commercially available ELISA kits according to manufacturer’s instruction. Nested PCR was done for HBV and RT-PCR for HCV, and HEV. Sequence and phylogenetic analyses were done using the Molecular Evolutionary Genetic Analyses version7.0 software (MEGA7). HBV DNA was quantified using real time PCR method and human cytokines gene expression was done using RT2 PCR array. Plasma cytokines were quantified using the magnetic beads multiplexed Luminex multiplex assay. Of the 82 patients recruited for this study, 49 (59.8%) were males, 33 (40.2%) females. There were 27 (32.9%) Malay patients, 51 (62.2%) Chinese, 3 (3.7%) Indians while the remaining 1 (1.2%) is orang asli. Majority of the patients, 41 (50%) are within the age of 50 and above, 32 (39%) within 30 to 49 years and the remaining 9 (11%) are below 30 years. The patients recruited for this study were classified as non-cirrhotic 44 (53.7%), cirrhotic 18 (22.0%), acute flare 17 (20.7%) and hepatocellular carcinoma 3 (3.7%). The rate of co-infection was found to be HBV+HEV (10.7%), HBV+HCV (1.3%), and 88% having single infection with HBV. Chemical profile revealed that majority (58%) have high level ALT (High (≥34 IU/L). Physical examination showed jaundice as the most frequent clinical symptoms followed by easy fatigability. A strong positive correlation was found between severity of infection and the level of AST (r=0.693; p<0.01) and jaundice (r=0.714; p<0.01). Similarly, moderate positive correlation was found between severity of infection and ALT (r=0.447; p<0.01) and serum bilirubin level (r=0.543; p<0.01). On the other hand, a negative correlation was found between severity of infection and total protein (r= -0.339; p<0.01) and albumin (r= -0.464; p<0.01). The results also showed that majority (62%) of the patients have high HBV DNA (>2000 IU/mL) and most of the patients with this high viral load were cirrhotic of acute flare. This HBV DNA load was found to correlate positively with hepatitis B e antigen titre (r= 0.950; p<0.01) and hepatitis B surface antigen titer (r= 0.642; p<0.01). This result showed that, HBV load correlated more with HBeAg titer than it does with HBsAg titer. Hence, the significance of HBeAg in monitoring patient progress on therapy in lieu of viral load in a situation where viral load is not available.Sequence analyses of the HBV shows that 63.9% of the virus belongs to genotype B and 36.1% genotype C. On the other hand, all HEV belong to genotype 4 while HCV belong to genotype 3a. Interestingly, the local HEV isolates UPM14, 23 and 45 demonstrated high sequence identity with a swine isolate, SAAS-FX17 (JF915746), from China (96.7%, 99% and 94.1%, respectively), while isolate UPM75 was found to be 89.3% identical to swine isolate IND-SW-00-01 (AY723745) from India. Cytokines gene expression results showedthat of the 84 genes associated with inflammatory pathways, only 7 (8.3%) genes were expressed among non-cirrhotic chronic hepatitis B patients compared with healthy hepatitis negative control group. Some genes were found to be upregulated, with acute flare group having highest number of upregulated genes and are associated with enhancing inflammatory process which might play a significant role in acute flaring of chronic hepatitis B patient. These upregulated genes include mostly pro-inflammatory chemokines such as Chemokine (C-C motif) ligands (CCL) and also interleukin receptor (IL-1R1) while anti-inflammatory cytokines genes such as interleukin 13, 17, as well as interleukin 1 receptor antagonist (IL-1RN) and gamma interferon were down regulated. Circulating IL-8(χ2=1351.05; DF=1197; p<0.005) and MIP-1beta (χ2=2302.99; DF=2142; p<0.05) were found to be significantly associates with the level of HBeAg. Similarly, hepatitis B viral DNA was also found to be significantly correlated with MIP-1beta (r=0.272; P<0.05). At the end of this study, an insight into the genetic distributions of hepatitis B, C and E viruses and the rate of HBV co-infection with HCV and HEV among Malaysian chronic hepatitis B patients was highlighted. It also described for the first time, comparative genomic sequence analyses of local HEV isolates suggesting a zoonotic origin with swine and boar HEV. Although, quantitative HBsAg and HBeAg has been identified as an important indicator of therapeutic response, this study revealed HBeAg as the most appropriate marker that correlate well with the HBV DNA. Up-regulation of the IL-3 gene in liver cirrhotic patients indicated poor prognosis and may be associated with the development of HCC. Similarly, this study, also suggested TNFSF-13 as a potential novel molecular prognostic marker in chronic hepatitis B patients. Circulating MIP-1beta was found to be a significant sero-marker in this study, therefore, it can be considered as a novel prognostic marker of liver cirrhosis in chronic hepatitis B patient.